Peran Lembaga Keuangan dalam Pemberdayaan Ekonomi Masyarakat - Hasyim; Manurung, Eka Valentina; Adelia, Fransiska; Sitio, Veranita; Nadapdap, Yemima E. (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study explores the role played by financial institutions in supporting community economic empowerment. In this context, the role of financial institutions is not only limited to traditional functions such as financial intermediation, but also involves important aspects such as financial inclusion, financial education, and access to financial services. This research analyzes the impact of active community participation in financial services on economic growth, poverty alleviation and increased welfare. The findings of this research provide insight into how financial institutions can be a catalyst for community economic development through various initiatives and programs that support accessibility, inclusiveness and understanding of the benefits of finance.